2017
DOI: 10.1111/bjh.14969
|View full text |Cite
|
Sign up to set email alerts
|

Renin‐angiotensin system blockade promotes a cardio‐renal protection in albuminuric homozygous sickle cell patients

Abstract: The management of sickle cell nephropathy (SCN) at an early stage is an important issue to prevent renal and cardiovascular morbidity and mortality. This study aimed to evaluate in this population, whether angiotensin converting enzyme inhibitors (ACEIs) treatment could exert a cardio-renal protection in a SCN cohort. Forty-two SCN patients (urine albumin:creatinine ratio (ACR) > 10 mg/mmol) were treated with ACEIs for 6 months, then evaluated for ACR, measured glomerular filtration rate (mGFR) together with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Urine albumin was reported in 1 RCT (n 5 22) 85 and 7 observational studies (total n 5 114). [86][87][88][89][90][91][92] In the 6 studies that examined ACEi therapy, 53 of 84 patients (63%) who received ACEi therapy showed improvement in urine albumin. [86][87][88][90][91][92] Of those who improved while receiving ACEi therapy, 18 (34%) had severe albuminuria (macroalbuminuria), 6 (11%) had moderate albuminuria (microalbuminuria), and the rest did not have their degree of albuminuria specified.…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Urine albumin was reported in 1 RCT (n 5 22) 85 and 7 observational studies (total n 5 114). [86][87][88][89][90][91][92] In the 6 studies that examined ACEi therapy, 53 of 84 patients (63%) who received ACEi therapy showed improvement in urine albumin. [86][87][88][90][91][92] Of those who improved while receiving ACEi therapy, 18 (34%) had severe albuminuria (macroalbuminuria), 6 (11%) had moderate albuminuria (microalbuminuria), and the rest did not have their degree of albuminuria specified.…”
Section: Recommendationmentioning
confidence: 99%
“…A total of 6 observational studies reported the treatment effect on blood pressure. [85][86][87]89,91,92 In 4 studies, 8 of 72 patients (11%)…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Although we did not screen for these genetic modifiers in our study, incorporating these modifiers may further enhance the screening accuracy for early detection of renal disease. Although new therapies have recently shown promising results in small studies in halting the progression of albuminuria and sickle nephropathy, 16,24,46,47 powered, controlled, randomized trials are still needed to evaluate the safety and efficacy of these therapies. Our study provides new insight into the natural progression of albuminuria in SCA that is needed for the successful design of such studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism remains unclear. Our data also suggest that, despite the successful use of ACEi in patients with SCA (Haymann et al, 2017), angiotensin receptor blockers might provide better renal protection. Theoretically, in addition to blocked Ang II formation, patients would benefit from enhanced formation of Ang-(1-7), converted from Ang II by ACE2.…”
mentioning
confidence: 55%